KONVERGENSI MEDIA LEMBAGA PENYIARAN PUBLIK: STUDI DESKRIFTIP PADA RRI PRO 2 MADIUN - Rahman, Fathur; Haryani, Nunik; Sejati, Veny Ari (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the application of media convergence by RRI Pro 2 Madiun in maintaining its existence in the digital era. The method used is qualitative descriptive with the main theories of Henry Jenkins, Terry Flew, and August Grant and Jeffrey Wilkinson. Data was collected through in-depth interviews, observations, and documentation of the institution's digital activities. The results of the study show that RRI Pro 2 has implemented economic, social, technological, cultural, and global convergence. This strategy can be seen in the integration of newsrooms, the use of platforms such as RRI Digital, YouTube, and Instagram, as well as cross-division collaboration. Key challenges include limited human resources, technological tools, and resistance to the old work culture. However, the opportunity to reach young audiences and expand public services is a key driver of digital transformation. This research is expected to contribute to the study of media communication and public broadcasting practices.